Design and Implementation of an Arduino-Based Bluetooth-Controlled Shopping Trolley with Ultrasonic Sensor Integration - Muhammad Hanafi; Almasri (Sagamedia Teknologi Nusantara, 2024)
Innovation in retail technology continues to evolve, aiming to enhance the shopping experience, particularly for customers with physical limitations. This research focuses on the design and implementation of an automated shopping cart system based on Arduino, controlled via Bluetooth using a smartphone. The system utilizes a Bluetooth HC-05 module for wireless communication, an ultrasonic HC-SR04 sensor for obstacle detection, and a motor driver to ensure smooth cart movement. The control application is developed using MIT App Inventor, offering navigation features such as forward, backward, left, and right turns. The ultrasonic sensor acts as a safety mechanism, detecting obstacles within 15 cm and providing warnings via a buzzer to prevent collisions. Testing results demonstrate high responsiveness and stable control over a distance of up to 10 meters. The findings of this study indicate that the automated shopping cart significantly improves convenience and accessibility, especially for customers with physical limitations, while ensuring a safer and more efficient shopping experience in supermarkets. This innovation presents a significant contribution to enhancing accessibility and operational efficiency in the retail sector.